2002
DOI: 10.2135/cropsci2002.8270
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Rate and Genotype Effect on Agronomic Performance and End‐Use Quality of Winter Wheat

Abstract: Few experiments have studied how seeding rates affect agronomic performance and end‐use quality of modern wheat (Triticum aestivum L.) genotypes in the Great Plains. Higher grain yield and better quality grain production requires the use of appropriate seeding rates. During the 1997 and 1998 crop seasons, 20 winter wheat genotypes and experimental lines were evaluated at two locations (four environments) to assess seeding rate and genotype effects on agronomic performance and end‐use quality of wheat. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
87
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 15 publications
18
87
6
Order By: Relevance
“…These results agree with findings of Geleta et al (2002), who reported significant differences among environments, seeding rates, genotypes, and some of their interactions. They found out that lower seeding rates decreased plant population, grain yield, kernel weight, flour yield, mixing time, caused later flowering, and increased flour protein content and mixing tolerance.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results agree with findings of Geleta et al (2002), who reported significant differences among environments, seeding rates, genotypes, and some of their interactions. They found out that lower seeding rates decreased plant population, grain yield, kernel weight, flour yield, mixing time, caused later flowering, and increased flour protein content and mixing tolerance.…”
Section: Resultssupporting
confidence: 92%
“…Results are in accordance with the findings of Geleta et al (2002). They pointed out that seeding rate is a predictable environmental factor that affects some agronomic and enduse quality traits of wheat; therefore, it should be studied carefully to obtain higher grain yields with better end-use quality.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Although the compensation by tillering can mitigate yield losses, tillers flower later than main stems. If there is insufficient time for tillers to mature there will be no yield benefit (Geleta et al 2002). Protein content is a function of the quantity of nitrogen (N) available to the wheat plant (Holford et al 1992) in combination with climatic conditions.…”
Section: á1mentioning
confidence: 99%